On-Chip Preconcentration Microchip Capillary Electrophoresis Based CE-PRM-LIVE for High-Throughput Selectivity Profiling of Deubiquitinase Inhibitors - Zhu, He; Mellors, J Scott; Chan, Wai Cheung; Thompson, J Will; Ficarro, Scott B; Tavares, Isidoro; Bratt, Ariana S; Decker, Jens; Krause, Michael; Kruppa, Gary; Buhrlage, Sara J; Marto, Jarrod A (Analytical chemistry, 2022)
The family of deubiquitinases (DUBs) comprises ∼100 enzymes that cleave ubiquitin from substrate proteins and thereby regulate key aspects of human physiology. DUBs have recently emerged as disease-relevant and chemically tractable, although currently there are no approved DUB-targeting drugs and most preclinical small molecules are low-potency and/or multitargeted. We paired a novel capillary electrophoresis microchip containing an integrated, "on-chip" C18 bed (SPE-ZipChip) with a TMT version of our recently described PRM-LIVE acquisition scheme on a timsTOF Pro mass spectrometer to facilitate rapid activity-based protein profiling of DUB inhibitors. We demonstrate the ability of the SPE-ZipChip to improve proteome coverage of complex samples as well as the quantitation integrity of CE-PRM-LIVE for TMT labeled samples. These technologies provide a platform to accurately quantify competitive binding of covalent and reversible inhibitors in a multiplexed assay that spans 49 endogenous DUBs in less than 15 min.
Keywords: Deubiquitinating Enzymes; Electrophoresis, Microchip; Proteome; elektroforéza mikročipová; deubikvitinasy; proteom; ubikvitin; Electrophoresis, Capillary; elektroforéza kapilární; Humans; lidé; Ubiquitin